Morphodynamics, genesis, and anthropogenically modulated evolution of the Elfeija continental dune field, arid southeastern Morocco - Amiha, Rachid (2025)
The Elfeija Dune Field (EDF) is a continental aeolian system in an arid region of southeastern Morocco. Studying this system is critical for understanding the effects of mounting climatic and anthropogenic pressures. This study provides a comprehensive characterization of the EDF’s morphology, sedimentology, aeolian dynamics, genesis, and recent evolution. A multi-scale, multidisciplinary approach was adopted, integrating field observations, sedimentological analyses, MERRA-2 reanalysis wind data, cartographic analysis, digital terrain modeling, and morphometric measurements. The results reveal an active 30 km2 dune field, elongated WSW-ENE, which is divisible into three morphodynamic zones with a high dune density (80–90 dunes/km2). The wind regime is predominantly from the W to WSW, driving a net ENE sand transport and creating conditions conducive to barchan formation (RDP/DP > 0.78). Sediments are quartz dominated, with significant calcite and various clay minerals (illite, kaolinite, and smectite). Dune sands are primarily fine- to medium-grained and well sorted, in contrast to the more poorly sorted interdune deposits. The landscape is dominated by barchans (mean height H = 2.5 m; mean length L = 50 m) and their coalescent forms, indicating sustained aeolian activity. The potential sand flux was estimated at 1.7 kg/m/s, with a dune collision probability of 32%. The field’s genesis is hypothesized to be controlled by a topographically induced Venturi effect, with an initiation approximately 1000 years ago, potentially linked to the Medieval Climatic Optimum. Significant anthropogenic impacts from expanding irrigated agriculture are observed at the dune field margins. By providing a detailed characterization of the EDF and its sensitivity to natural and anthropogenic forcings, this study establishes a critical baseline for the sustainable management of arid environments.